Controversial New Sciences in the Media: Content Analysis of Global Reporting of Nanotechnology during the Last Decade. Issue 1 (February 2014) - Fisk, Kylie; Fitzgerald, Richard; Cokley, John
The potentially controversial science of nanotechnology is only now beginning to infiltrate mainstream public consciousness through media channels. This article suggests the infiltration is taking different forms, depending on the nationality of journalists reporting on the science. Having completed analysis of a large longitudinal international sample of news and feature articles about nanotechnology, we report that journalists in Australia and New Zealand deploy sources 'direct from the lab' to highlight scientific advancements; those in Asia emphasise the nation-building potential of nanotechnology; US journalists provide positive coverage across all areas; and those in the United Kingdom offer the most critical analysis and risk reporting. These messages have also evolved over time in each region. Results are integrated with existing research about public perceptions of nanotechnology, and suggest several themes common to all media reporting of nanotechnology, the most important of which reflects positive reporting or acceptance, although safety concerns and health risks also arise.